Examining the impact of financial development on load capacity factor (LCF): System GMM analysis for Asian economies - Latif, Nazia; Faridi, Muhammad Zahir (Frontiers in Energy Research, 2023)
Contingent upon the empirical work done current study seeks to investigate the environmental (LCF) consequences of financial development in three different ways for 48 Asian economies. We use the two-step system GMM technique to analyze the data from 1996 to 2020. Initially, the study investigated the environmental consequences of financial development by taking six dimensions of financial development. Then we modify the original EKC (Environmental Kuznets Curve) into the financial market-based EKC (FM_EKC) to compare the short-run and long-run environmental consequences of financial development. Ultimately the study explores the marginal effect of financial development on environmental quality moderated by the role of institutional quality. The key findings of the System GMM analysis confirmed that Asian countries have an inverted U shape FM_EKC. It observes that the strong institutional structure in an economy guarantees the favorable environmental consequences of financial development in the long run. It is also suggested that a healthier education structure of an economy can help to improve the environmental quality of an economy.